A Two-Stage Efficiency Analysis of Rail Passenger Franchising in Germany - Heike Link (Journal of Transport Economics and Policy, 2016)
This paper analyses the differences in the efficiency of using subsidies for franchised regional rail services between the federal states in Germany, and provides evidence on the impact of procurement strategies and contractual design on the efficient use of funds. The analysis is based on a 15-year panel data set at the level of the federal states and employs a two-stage efficiency analysis, including a DEA approach and a Tobit panel model. The analysis shows that a higher share of tendering, a higher share of gross contracts, and longer and smaller contracts were efficiency-enhancing factors in the period of analysis.
Keywords: 330; Eisenbahnverkehr; Franchising; Schienenverkehr; Wirtschaftlichkeit; Deutschland